Linguistic Patterns Among Pop Culture Discourse on @westenthu X or Twitter Platform - Arsita Julianda Guswi; Annissa Ramadhani; Aryo Mulyo Satrio Negoro; Teguh Sarosa (JELITA, 2025)
This study examines how pop culture enthusiasts use language on the @westenthu auto-base account to express identity and foster community in digital spaces. Tweets from October 3 to October 5, 2024, are analysed qualitatively through document analysis to identify linguistic patterns, contextual usage, and cultural dynamics. The limited timeframe was chosen to ensure a focused, detailed examination of interactions without overwhelming data volume, which is essential for qualitative research. Findings reveal the frequent use of code-switching, code-mixing (e.g., “drop ur fav Christmas wst movies yang seru plss”), slang (e.g., “nonton Princess Diaries dimana ya? Tia!”), and informal language, illustrating the dynamic interplay between language and identity in online communication. These linguistic practices show how platforms like X (formerly Twitter) not only facilitate interaction but also create spaces for identity construction and rapid language evolution. By analysing specific language features, this research offers insights into the intersection of sociolinguistics and digital communication, highlighting how language adapts and thrives in digital environments.